2015
DOI: 10.1063/1.4918627
|View full text |Cite
|
Sign up to set email alerts
|

Dopant controlled trap-filling and conductivity enhancement in an electron-transport polymer

Abstract: Charge transport in organic semiconductors is often inhibited by the presence of tail states that extend into the band gap of a material and act as traps for charge carriers. This work demonstrates the passivation of acceptor tail states by solution processing of ultra-low concentrations of a strongly reducing air-stable organometallic dimer, the pentamethylrhodocene dimer, [RhCp*Cp]2, into the electron transport polymer poly{[N,N′-bis(2-octyldodecyl)-naphthalene-1,4,5,8-bis(dicarboximide)-2,6-diyl]-alt-5,5′-(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 31 publications
2
55
0
Order By: Relevance
“…[52] This coupling of electron-transfer and bond-cleavage processes results in materials that are moderately air stable, despite their strongly reducing character. Both of these compounds have been used as dopants for organic semiconductors [53][54][55] and for reducing the work function of oxide electrodes. [56,57] Pentamethylrhodocene dimer has also been recently demonstrated to dope SLG, causing the work function to decrease by 1.29 eV.…”
Section: Ev)mentioning
confidence: 99%
“…[52] This coupling of electron-transfer and bond-cleavage processes results in materials that are moderately air stable, despite their strongly reducing character. Both of these compounds have been used as dopants for organic semiconductors [53][54][55] and for reducing the work function of oxide electrodes. [56,57] Pentamethylrhodocene dimer has also been recently demonstrated to dope SLG, causing the work function to decrease by 1.29 eV.…”
Section: Ev)mentioning
confidence: 99%
“…11,12 Nevertheless a few stable n-type dopants have been reported via mechanisms other than integer charge transfer. [13][14][15][16][17][18][19][20][21][22][23][24][25] For example the addition of 1H-benzimidazole or benzimidazolium salts has succeeded in tuning of the work function of graphene and the conductivity of fullerene derivatives. 13,26 Mechanistic studies in the solution phase found that the dopant reacted with the fullerene derivative through hydride or hydrogen atom transfer to afford host radical anions, which were responsible for the doping effect.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the symmetric gold-organic-gold structure ensures that there is no built-in potential in the measured device. Finally, we introduce a new procedure to resolve the problem of the electrode-organic injection barrier, [32] and form Ohmic contacts in the planar structure, without which the Ohmic region of the I-V characteristics cannot be accessed. The lack of ohmicity is clearly shown with the black curve of Figure 7b, which corresponds to the current obtained using Au only as the hole-injection contact for Spiro-TAD.…”
Section: Introductionmentioning
confidence: 99%